2011
DOI: 10.1590/s0100-40422011000100019
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de processo de produção de conjuntos eletrodo-membrana-eletrodo para células a combustível baseadas no uso de membrana polimérica condutora de prótons (PEMFC) por impressão a tela

Abstract: . Proton exchange membrane fuel cell (PEMFC) requires membrane electrode assemblies (MEA) to generate electrical energy from hydrogen and oxygen. In this study a MEA production process by sieve printing and an ink composition were developed to produce catalyst layers of MEAs. The deposition of the exact catalyst content was possible on cathodes and anodes with only one print step. The optimal ink developed shown viscosity of 2.75 Pa s, density 1.27 g cm -3 , total solid content of 33.76 % and tack of 92 U.T. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
14

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 10 publications
2
2
0
14
Order By: Relevance
“…The current densities obtained between 25 and 90 C were similar to those obtained with commercial Pt/C with 35% NI w, our usual formulation to this catalyst [43,69,75]. Above 90 C, performance losses occurred due to accumulation of water in the single fuel cell used [43,69,75]. From Fig.…”
Section: Single Fuel Cell Evaluationsupporting
confidence: 69%
See 3 more Smart Citations
“…The current densities obtained between 25 and 90 C were similar to those obtained with commercial Pt/C with 35% NI w, our usual formulation to this catalyst [43,69,75]. Above 90 C, performance losses occurred due to accumulation of water in the single fuel cell used [43,69,75]. From Fig.…”
Section: Single Fuel Cell Evaluationsupporting
confidence: 69%
“…5 and 6 it was found that, similar to the study with Pd/C in both electrodes [83], MEA with synthesized Pt/C on cathode using values between 55 and 60% NI w resulted in higher performance. The current densities obtained between 25 and 90 C were similar to those obtained with commercial Pt/C with 35% NI w, our usual formulation to this catalyst [43,69,75]. Above 90 C, performance losses occurred due to accumulation of water in the single fuel cell used [43,69,75].…”
Section: Single Fuel Cell Evaluationsupporting
confidence: 58%
See 2 more Smart Citations
“…1 Tal interesse é justificado pela crescente preocupação com a degradação ambiental e com a necessidade de substituir os combustíveis provenientes de fontes não renováveis. 2 Desta forma, a geração de energia elétrica utilizando células a combustível surge como uma promissora alternativa, tanto para a aplicação como fontes estacionárias (indús-trias, hospitais, residências, etc.) como fontes móveis (veículos).…”
Section: Introductionunclassified